Cardiac Tissues From Stem Cells: New Routes to Maturation and Cardiac Regeneration - Campostrini, Giulia; Windt, Laura M; van Meer, Berend J; Bellin, Milena; Mummery, Christine L (Circulation research, 2021)
The ability of human pluripotent stem cells to form all cells of the body has provided many opportunities to study disease and produce cells that can be used for therapy in regenerative medicine. Even though beating cardiomyocytes were among the first cell types to be differentiated from human pluripotent stem cell, cardiac applications have advanced more slowly than those, for example, for the brain, eye, and pancreas. This is, in part, because simple 2-dimensional human pluripotent stem cell cardiomyocyte cultures appear to need crucial functional cues normally present in the 3-dimensional heart structure. Recent tissue engineering approaches combined with new insights into the dialogue between noncardiomyocytes and cardiomyocytes have addressed and provided solutions to issues such as cardiomyocyte immaturity and inability to recapitulate adult heart values for features like contraction force, electrophysiology, or metabolism. Three-dimensional bioengineered heart tissues are thus poised to contribute significantly to disease modeling, drug discovery, and safety pharmacology, as well as provide new modalities for heart repair. Here, we review the current status of 3-dimensional engineered heart tissues.